PENGEMBANGAN MEDIA BUKU CODING FOR KIDS UNTUK MENINGKATKAN PROBLEM SOLVING ANAK USIA 5-6 TAHUN DI TK KECAMATAN BAHAR UTARA - Septiana, Reni; Hasni, Uswatul; Nur Ismiatun, Asih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Problem solving is a basic skill that is important for early childhood to have in carrying out daily activities. Therefore, interesting and innovative learning media are needed to help improve children's problem solving, one of which is through the media of coding books for kids. This study aims to determine what is needed in making coding books for kids to improve the problem solving skills of children aged 5-6 years, produce coding book media for kids that are suitable to improve problem solving of children aged 5-6 years in kindergarten in Bahar Utara District, and determine teacher responses to coding book media for kids to improve problem solving of children aged 5-6 years in kindergarten in Bahar Utara District. This study uses the Research and Development (R&D) method with the ADDIE model. Data were obtained through expert validation and teacher responses. The results of material expert validation were 97% and media expert validation were 85%. In addition, the results of the practicality test by teachers showed a percentage of 84.89% in the large group and 92.59% in the small group with very good criteria.